Profile of patients attended as psychiatric emergencies at a university general hospital - Padilha, Vitoria Mantoan (2013)
CONTEXT AND OBJECTIVE: The prevalence of psychiatric conditions in clinical settings is high, particularly in emergency services. This is a challenge for healthcare professionals and an essential element in the functioning of the mental health network. The objective here was to describe the sociodemographic and clinical profile and the practices among patients treated psychiatrically in the Emergency Unit. DESIGN AND SETTING: Descriptive and quantitative study, conducted at Hospital das Clínicas (HC), Universidade Estadual de Campinas (Unicamp). METHODS: Sociodemographic data, reasons for attendance, diagnostic hypotheses and practices were analyzed. RESULTS: Psychiatric staff attended 1,835 cases over the study period, corresponding to 1465 patients. The patients were predominantly women (53.7%) and white (79.6%); their mean age was 37 years and 41.3% lived with their parents. The commonest reasons for attendance were depressive symptoms (28.1%), agitation (23.6%) and problems with psychoactive substances (19.5%). The commonest diagnoses were psychoactive substance-related disorders (23%) and depressive disorders (18.5%). 31.6% of the patients were referred to healthcare centers and 29.2% to specialized outpatient clinics, while 8.2% were hospitalized. CONCLUSIONS: This study emphasizes that it is important for professionals working in emergency service to have information about the patients’ profile and the main reasons that lead them to seek psychiatric care, and to establish a diagnosis that will allow proper management at the emergency service and case referral.